Contributions and perspectives of chicken genomics in Brazil: from biological model to export commodity - Jorge, E. C.; Figueira, A.; Ledur, M. C.; Moura, Ana Silvia Alves Meira Tavares [UNESP]; Coutinho, L. L. (Cambridge University Press, 2007)
Chicken is one of the most important sources of animal protein for human consumption, and breeding programmes have been responsible for constant improvements in production efficiency and product quality. Furthermore, chicken has largely contributed to fundamental discoveries in biology for the last 100 years. In this article we review recent developments in poultry genomics and their contribution to adding functional information to the already existing structural genomics, including the availability of the complete genome sequence, a comprehensive collection of mRNA sequences ( ESTs), microarray platforms, and their use to complement QTL mapping strategies in the identification of genes that underlie complex traits. Efforts of the Brazilian Poultry Genomics Programme in this area resulted in generation of a resource population, which was used for identification of Quantitative Trait Loci ( QTL) regions, generation of ESTs and candidate gene studies that contributed to furthering our understanding of the complex biological processes involved in growth and muscular development in chicken.
Keywords: EST; microarray; muscle development; poultry genetics; QTL mapping